Beekeeping under the Italian legal system - Różański, Krzysztof (Przegląd Prawa Rolnego, 2018)
The aim of the article was to familiarise the readers with the Italian regulations and doctrine concerning beekeeping. The systematics contained in Act No. 313 of 24 December 2004 on apiculture has been analysed. Article 3 of this Act determines the agricultural character of the apiculture activity, qualifying it as an agricultural activity in the light of Article 2135 of the Civil Code. Migratory beekeeping, also classified as a related agricultural activity, consists in the relocation of bees to different regions of the country in order to increase crop productivity. Further, Act No. 313 provides legal definitions of basic institutions related to apiculture and introduces various forms of protection and support for this activity, including those from the apiculture sector. The solutions adopted by the Italian legislator constitute an interesting material for the Polish legislator to examine with regard to the possibility of introducing amendments to the regulation of the domestic beekeeping sector.